Houseman's Duties and Responsibilities in Cleaning Public Areas in the Housekeeping Department of Grand Cityhall Hotel & Serviced Residences Medan - Samosir, Batara Sahala Doli (Cattleya Darmaya Fortuna, 2024)
A houseman is a staff member in the housekeeping department responsible for maintaining the cleanliness, aesthetics, orderliness, and comfort of all hotel areas, excluding guest rooms and the kitchen. This role covers a wide area, both inside and outside the hotel building, which presents a significant responsibility for the houseman. This research employs a descriptive quantitative method, with data collected through direct field observations and interviews. The study was conducted at the research location with a population of 13 individuals, consisting of 1 supervisor, 6 housemen, and 6 hotel guests. The findings indicate that the housemen's performance in maintaining cleanliness is not yet optimal. Common issues include a lack of attention to the correct functions and dosages of cleaning materials and poor discipline in storing tools and materials after use. Based on these findings, it is recommended that housemen improve their awareness of work outcomes, adhere to the proper usage of cleaning supplies, and maintain discipline in organizing cleaning tools and materials. This will ensure a neater storage area and enhance overall service quality in the hotel environment.